(untitled) (Journal of Fatima Jinnah Medical University, 2018)
We treated surgically 16 patients with symptomatic complete dislocation of the acromioclavicular joint. The surgical procedure included debridment of Ac jaoint, reconstruction of the coracoclavicular ligament with multistrand vicryl band, repair of the acromioclavicular ligament, and imbrications of the deltotrapezius aponeurosis over the top of the distal clavicle. A temporary K wire fixaton of acromioclavicular joint was used to stabilize the joint. One patients was lost to follow-up.15 patients were followed for an average of 6 months (4–8 months). Functional outcome was assessed according to Imatani acromioclavicular rating scale. The results were excellent in 12 patients, good in two, and poor in one. Superficial infection (k-wire entry point) occurred in four patients which was treated with antibiotics, wound care and removal of k-wires around 4thweek after surgery. Laterl migaraiton of K wire occured in one patient In two patients, there was loosening of the Kwires where subluxation occured in five cases and complete dislocation in one two cases.